The reality of electronic libraries in Sudanese universities - El Fadel, Mohamed Ibrahim Mohamed; Mohamed, Fathi Saad; Ahmed, Al-Chalabi Mohammed (Arab Journal for Sciences and Research Publishing, 2017)
The research attempted to identify the reality of electronic libraries in Sudanese universities, and the most important Detection of the main obstacles faced to reach results that will create a modern model for the future library, so as to face the dam informatics needs of the academic community in universities, and to support the educational process and research programs. The researcher followed the descriptive method as the basis for the review of the literature by generously intellectual production، the interview to find out the reality of the electronic university libraries and Obstacles questionnaire. And the research found the following findings: The electronic university libraries with the lack of availability were not the specifications that meet the need of users. And the Research presents envisioned of a modern model for future electronic library in Sudanese universities. And then the researcher presented the most important recommendations in the following: The necessity of benefiting of future library model prepared by research in the development and creation of electronic libraries of various universities. Necessity of training courses on how to optimize the use of electronic library for future librarians and other beneficiaries.